Growth aspirations and social capital: Young firms in a post-conflict environment. (August 2015) - Efendic, Adnan; Mickiewicz, Tomasz; Rebmann, Anna
This article explores the growth aspirations of owners and managers of young firms in a post-conflict economy by focusing on social capital. It treats social capital as a multidimensional, multilevel phenomenon, studying the effects of discussion network characteristics, trust in institutions, generalised trust in people and local ethnic pluralism. We argue that in a post-conflict country, ethnic pluralism is indicative of local norms of tolerance towards experimentation and risk taking which support growth aspirations. It also distinguishes between the aspirations of hired managers and owners-managers. The empirical counterpart and hypotheses testing rely on survey evidence drawn from young businesses in Bosnia and Herzegovina.